Effect of torrefaction on the properties of rice straw high temperature pyrolysis char: Pore structure, aromaticity and gasification activity. (March 2017) - Chen, Handing; Chen, Xueli; Qin, Yueqiang; Wei, Juntao; Liu, Haifeng
Highlights: Specific surface area of char decreases with torrefaction severity for raw straw. Torrefaction leads to lower graphitization degrees of pyrolysis char for raw straw. The influence of torrefaction is different between raw and water washed straw. Pyrolysis char of torrefied sample above 250 °C owns a lower gasification activity. Abstract: The influence of torrefaction on the physicochemical characteristics of char during raw and water washed rice straw pyrolysis at 800–1200 °C is investigated. Pore structure, aromaticity and gasification activity of pyrolysis chars are compared between raw and torrefied samples. For raw straw, BET specific surface area decreases with the increased torrefaction temperature at the same pyrolysis temperature and it approximately increases linearly with weight loss during pyrolysis. The different pore structure evolutions relate to the different volatile matters and pore structures between raw and torrefied straw. Torrefaction at higher temperature would bring about a lower graphitization degree of char during pyrolysis of raw straw. Pore structure and carbon crystalline structure evolutions of raw and torrefied water washed straw are different from these of raw straw during pyrolysis. For both raw and water washed straw, CO2 gasification activities of pyrolysis chars are different between raw and torrefied samples.